Evaluation of the level of Some Heavy Metals in Tobacco of Domestic and Imported Cigarette Brands Used in Iraq (Baghdad Science Journal, 2015)
Smoking-related diseases can be attributed to the inhalation of many different toxins, including heavy metals, which have a host of harmful health effects. The primary objective of this study was to determine whether local and imported cigarette brands used in Iraq , have they elevated levels of metals or not .Three metals Lead (Pb) , Cadmium (Cd) and Chromium(Cr) were determined in tobacco of seventeen brands of imported cigarettes commonly available in Iraq and three Iraqi domestic cigarettes , which were randomly taken from retail market in Baghdad by using flame atomic absorption spectrometry. The produced data of imported and local cigarette brands were discussed and compared together and with studies from elsewhere .The results obtained showed that mean concentrations of lead for all cigarette brands was 5.87 ?g/g dry weight (range 2.27-11,67 ?g/g) , cadmium 0.57?g/g dry weight (range 0.1-1.57 ?g/g) and chromium 3.77?g/g dry weight (range 0.0-11.21 ?g/g) ..There was a large variability in Pb, Cd and Cr content of samples of cigarettes. Pb concentration was the highest, followed by Cr while Cd was the lowest. The investigation confirmed that most of the Iraqi and imported cigarettes in Iraq are contaminated with Pb, Cd, and Cr and quantitatively their distribution is clearly above the safer limits of WHO.